1997
DOI: 10.1590/s0100-879x1997000400006
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide and feeding activity patterns in rats

Abstract: This review presents historical data about atrial natriuretic peptide (ANP) from its discovery as an atrial natriuretic factor (ANF) to its role as an atrial natriuretic hormone (ANH). As a hormone, ANP can interact with the hypothalamic-pituitary-adrenal axis (HPA-A) and is related to feeding activity patterns in the rat. Food restriction proved to be an interesting model to investigate this relationship. The role of ANP must be understood within a context of peripheral and central interactions involving diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
5
1
Order By: Relevance
“…Recently, we demonstrated that the circadian variations in plasma ANP and corticosterone are similar in rats fed ad libitum or on a restricted feeding schedule (18). The disagreement between our previous results of ANP daily variation in rats and the present result in humans suggests a possible physiological difference between species.…”
contrasting
confidence: 92%
“…Recently, we demonstrated that the circadian variations in plasma ANP and corticosterone are similar in rats fed ad libitum or on a restricted feeding schedule (18). The disagreement between our previous results of ANP daily variation in rats and the present result in humans suggests a possible physiological difference between species.…”
contrasting
confidence: 92%
“…Thus, the inhibition of water intake may be part of a larger, or more general, phenomenon and may not be specific to water intake. Newly emerged evidence showed that ANP also played a role in modulating feeding activity patterns in rats [24]. A study by Tarjan showed intracerebral administration ANP not only inhibited water and salt intake, but reduced food intake, suggesting ANP may centrally inhibit food intake [25].…”
Section: Discussionmentioning
confidence: 99%
“…Along this line of reasoning, it has been demonstrated that ANP release occurs with a pulsatile pattern during the circadian cycle, in which secretory peaks anticipate food ingestion and daily activity (Oliveira et al 1993, 1997). Collectively, the present observations together with previous studies suggest that the increase in the rhythmic activity of 5‐HTergic neurones in DRN appears to modulate renal efferent mechanisms.…”
Section: Discussionmentioning
confidence: 99%